Tales from the Peloton: Stress and coping in professional women`s road cycling - Vaughan, S.; McEwan, H. E.; Beggan, A.; Whitehead, A. E. (Psychology of Sport and Exercise, 2025)
Objective The purpose of this study was to use narrative inquiry to explore professional women cyclist's stories of stress and coping from their race experiences.